ANALISIS PROSES PENGELOLAAN KEUANGAN PADA USAHA MIKRO DAN KECIL (STUDI PADA USAHA TOKO/KIOS SEMBAKO DI KECAMATAN KOTA WAINGAPU) - Shilvia Rambu Kudu; Linda Rambu Kuba Yowi (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2020)
The sector of micro, small and medium enterprises (MSMEs) in Indonesia is always developing. However, there are still MSMEs that experience difficulties in terms of marketing, limited financial capital, limited resources (HR), limited raw materials and limited information technology. But the main problem is the problem of financial management, there are still many MSMEs that are wrong in separating business finance and personal and there are still many businesses that do not make financial statements. The purpose of this study is to find out the financial management process carried out by micro and small businesses. This research was conducted in Kota Waingapu Subdistrict in a food store / kiosk business. This type of research is caulitative research where this study does not use the term population but uses the social situation designation. The sampling technique in this study by looking at the data taken has been saturated and the sample no longer provides new information so that 8 informants were interviewed. The data analysis technique used in this study is the analysis technique of Miles & Humbermad models. This data analysis technique consists of three stages: data reduction, data presentation and conclusion drawing From the results of this study indicate that micro and small businesses / food shops do not all business actors implement a financial management process consisting of four indicators, namely planning, recording, reporting and controlling. Indicators of financial management that are not carried out are reporting. While the recording indicators that are not carried out are recording sales transactions and not storing proof of cash inflows.